MENGENALI NARASI DALAM SENI RUPA - Acep Iwan Saidi (Jurnal Sosioteknologi, 2007)
This article presents a preliminary study on narration in fine arts. In this article, a brief explanation on what is meant by narration is discussed. The explanation is based on the traditions used in the literature domain. Unlike the narration in the literature, the literature in fine arts has its own specific characteristics, among others, sinecdoce part pro toto, symbolic, incomplete narrative elements, present as well as absent, and formed by other visual element relation. In this study, however, the analysis on the structure of the narration was focused by using various literature theories. Key word: narration, symbol, relation, visual element